The MUSIC model of motivation: Its utilization in the e-learning context and graduate students’ perceptions of its effectiveness - Shemy, Nader Said; Dalioglu, Seray Tatli (Journal of Education and e-Learning Research, 2023)
The current study aimed to evaluate an online learning experience based on the music model of motivation in an educational technology post-graduate program in Oman. In order to understand the motivational perceptions of students regarding the instruction, a two-phase, sequential explanatory mixed method research design was conducted in this study. The quantitative data was collected from 40 students who enrolled in one class in which the instructional design was implemented for 2 weeks. After collecting the quantitative data, 10 students who voluntarily participated in the study's second phase were asked to respond to open-ended questions. The quantitative and qualitative data were interpreted and reported together by researchers. In conclusion, this research revealed that instructional design based on the music model of motivation is effective in increasing the motivation of students for each component of the model. Therefore, the researchers recommended expanding the use of the music model in the context of e-learning especially with part- time postgraduate students.